Examining the nutritional habits of individuals with moderate and severe covid-19, evaluation of changing nutritional habits and physical activity behavior after covid-19 - ÇAĞLAYAN, NİLAY; Nacar, Erkay (Scientific Reports in Medicine, 2025)
Objective: This research aimed to examine the eating habits of adult individuals infected with severe and moderate COVID-19 disease and to evaluate the changing eating habits and physical activity behaviors of post-COVID-19 individuals.Methods: The cross-sectional study included 1340 people over the age of 18 and had a positive PCR test. The data was collected online with the ”Google Form". The obtained data were analyzed with the statistical package program SPSS 25 (Statistical Package for Social Science). Data Mean±Standard Deviation and percentage distribution and the Chi-square test were used in its analysis. p
Keywords: COVID-19; Nutrition habits; Nutrition